2018
DOI: 10.15835/nbha47111375
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Capacity, Total Phenols, Total Flavonoids and Colour Component of Cornelian Cherry (Cornus mas L.) Wild Genotypes

Abstract: A number of selected cornelian cherry wild genotypes were investigated regarding antioxidant capacity, total phenols, total flavonoids and colour component. The total phenolic, total flavonoids and antioxidant activity of methanol extract of cornelian cherry fruits were determined using Folin-Ciocalteu, colorimetric and DPPH methods, respectively. Total phenolic content ranged from 163.69 (S1) to 359.28 (H2) mg GAE 100 g-1 FW. Genotypes H2 and H3 had the highest total phenolic content (359.28 and 343.50 mg GAE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 19 publications
3
28
0
2
Order By: Relevance
“…These proceedings are consistent with Yilmaz et al's paper, in which they showed how the polyphenol concentration was genetically related [3]. Polyphenol content can be linked to the amount of juice and peel color [30,36,37]. Cultivar Szafer possessed the most intense purple color of all cultivars, and it was also the richest in TPC among the cultivars tested by Kucharska et al In the study by Adamenko et al [38], an analogous relationship could be noticed in meads prepared with different Cornus mas juices with different colors ranging from amber yellow to red.…”
Section: Phytocompounds Composition In Cornelian Cherry Fruitssupporting
confidence: 89%
“…These proceedings are consistent with Yilmaz et al's paper, in which they showed how the polyphenol concentration was genetically related [3]. Polyphenol content can be linked to the amount of juice and peel color [30,36,37]. Cultivar Szafer possessed the most intense purple color of all cultivars, and it was also the richest in TPC among the cultivars tested by Kucharska et al In the study by Adamenko et al [38], an analogous relationship could be noticed in meads prepared with different Cornus mas juices with different colors ranging from amber yellow to red.…”
Section: Phytocompounds Composition In Cornelian Cherry Fruitssupporting
confidence: 89%
“…Total Phenolic Content Cosmulescu et al (2019) reported TPC values between 163.69 and 359.28 mg GAE/100 g, FW for wild Cornelian cherry genotypes. In another study, TPC of polar fraction and methanolic extract for fresh Cornelian cherry was determined as 439.9 ± 34.6 mg GAE/100 g and 2,110 ± 84.0 mg GAE/100 g respectively (Karaaslan et al, 2018).…”
Section: Physicochemical Compositionmentioning
confidence: 99%
“…Gallic acid and ellagic acid contents in our sample were found to be higher compared with these results. Cosmulescu et al (2019) also examined the phenolic compounds of wild Cornelian cherry fruit genotypes. Among the individual phenolic compounds, gallic acid was determined in higher amount (14.49 mg/100 g), followed by coumaric acid (13.79 mg/100 g), ellagic acid (5.71 mg/100 g), salicylic acid (1.43 mg/100 g), ferulic acid (1.25 mg/100 g) and synaptic acid (0.19 mg/100 g).…”
Section: Phenolic Profile Of Garagurt Extractmentioning
confidence: 99%
“…Cornelian cherry fruits contain significant amounts of phenolic bioactive substances, which contribute to their antioxidant value. In our study, the lowest total polyphenols were found in the fruits of the Chisinau yellow variety 183.91 mg/100 g, and the highest in the fruits of the selection Krupnoplodni NS 307.9 mg/100 g. The content of total polyphenols in Cornelian cherry fruits from Bosnia and Herzegovina studied by Drkenda et al [46] ranged from 119.1 to 230.6 mg GAE/100 g FW, and in fruits from Romania shown by Cosmulenca et al [59] from 163.7 to 359.28 mg GAE/100 g FW, which is close to results presented in this paper. Much wider variation in the content of total polyphenols in Cornelian cherry fruits was presented by Stanković et al [60] from 12.8 to 341.1 mg GAE/100 g FW.…”
Section: Biochemical Characteristicsmentioning
confidence: 84%